Cover Feature: Trópos and Átropos Biindole Chiral Electroactive Monomers: A Voltammetry and HPLC Comparative Insight (ChemElectroChem 6/2022). Issue 6 (14th February 2022) - Arnaboldi, Serena; Grecchi, Sara; Vaghi, Luca; Penoni, Andrea; Scapinello, Luca; Buzzi, Ivo Franco; Cirilli, Roberto; Pierini, Marco; Benincori, Tiziana; Mussini, Patrizia Romana
Abstract : The Cover Feature illustrates 2, 2'‐biindole‐based inherently chiral electroactive monomers and their 3, 3' analogues as an excellent study case of two equivalent redox centres interacting through a torsional barrier. The 3, 3' monomers, featuring large twin peak splittings in CV, are "trópos" systems with a low torsional barrier, so they cannot exist as stable enantiomers at room temperature. Instead, their 2, 2' isomers, with much smaller twin peak splittings, are "átropos" systems and can be separated by enantioselective HPLC into stable enantiomers, providing powerful "inherently chiral" selectors with outstanding enantioselection properties in chiral electroanalysis and electrochemistry as well as in chiroptical spectroscopy, with fascinating reciprocal correlations. More information can be found in the Article by S. Arnaboldi et al .